Quantitative process control theory - Zhang, Weidong, 1967- (Automation and control engineering., 2012)
"Preface Since the Industrial Revolution, control systems have played important roles in improving product quality, saving energy, reducing emission, and relieving the drudgery of routine repetitive manual operations. In the past hundred years, many theories have been proposed for control system design. However, there are three main problems when some of these advanced control theories are applied to industrial systems: 1. These theories depend on empirical methods or trial-and-error methods in choosing weighting functions. 2. Both the design procedures and results are complicated for under- standing and using. 3. The controllers cannot be designed or tuned for quantitative engineering performance indices (such as overshoot or stability margin). In this book, an improved theory called the Quantitative Process Control Theory is introduced to solve these problems. This new theory has three features: 1. When using the theory, the designer is not required to choose a weighting function. 2. The design is suboptimal and analytical. It is easy to understand and use. 3. The controllers can be designed or tuned for quantitative engineering performance indices. Mathematical proofs are provided in this book for almost all results, especially when they contribute to the understanding of the subjects presented. This will, I believe, enhance the educational value of this book. During the procedure of writing, as few concepts as possible are introduced and as few mathematical tools as possible are employed so as to make the book accessible. Examples are presented at strategic points to help readers understand the subjects discussed. Chapter summaries are included to highlight the main problems and results"--Provided by publisher